Effects of mechanical pre-bloom defoliation on cordon de Royat pruned Sangiovese (Vitis vinifera L.) vines - Ilaria Filippetti; Gianluca Allegro; Gabriele Valentini; Chiara Pastore; Stefano Poni; Cesare Intrieri (OENO One, 2011)
Aims: Recent trials on Sangiovese vines have shown that hand defoliation of shoot basal leaves at pre-bloom is effective in reducing fruit set and yield, leading to better grape composition and quality. The present work was performed to assess whether similar outcomes could be obtained by a more economically viable mechanical approach, which appears to be extremely attractive in cultivars such as Sangiovese, marked by high or very high yield potential and heavy, fairly compact clusters quite sensitive to rot. Methods and results: The trial was designed to compare pre-bloom mechanical defoliation (MD), hand defoliation (HD) and no defoliation (C) on Sangiovese vertical shoot positioned and spur pruned cordon de Royat trained vines. In the HD treatment, the first six basal leaves of each shoot were removed (70 % of leaf area), whereas in the MD treatment 33 % of the leaf area was removed from the basal part of the shoots. HD and MD compared to C reduced fruit set (HD = 29.8%; MD = 24.2%; C = 35.5 %), yield per shoot (HD = 546 g; MD = 516 g; C = 764 g), cluster weight (HD = 292 g; MD = 272 g; C = 382 g) and berry weight (HD = 2.17 g; MD = 2.31 g; C = 2.45 g), but improved total soluble solids (HD = 23.0 °Brix; MD = 22.5 °Brix; C = 20.8 °Brix) and total anthocyanins (HD = 837 mg/kg of grapes; MD = 744 mg/kg of grapes; C = 647 mg/kg of grapes). Leaf photosynthesis, measured in 2007, increased only temporarily after HD and MD as compared to control. Conclusions: The pre-bloom HD of shoot basal leaves confirmed its positive effect on crop yield control and grape composition, leading to better grape quality. The pre-bloom MD of the basal part of the shoots maintained most of the advantages associated with HD, although only half of the leaf area removed by hand was removed by the machine. Significance and impact of the study: Pre-bloom mechanical defoliation can replace hand defoliation and partially replace the time-consuming and costly manual cluster thinning technique, which is often used in high yield cultivars such as Sangiovese.